2005
DOI: 10.1038/nature03918
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of p53-dependent cellular senescence in suppression of Pten-deficient tumorigenesis

Abstract: Cellular senescence has been theorized to oppose neoplastic transformation triggered by activation of oncogenic pathways in vitro 1-3 , but the relevance of senescence in vivo has not been established. The PTEN and p53 tumour suppressors are among the most commonly inactivated or mutated genes in human cancer including prostate cancer 4,5 . Although they are functionally distinct, reciprocal cooperation has been proposed, as PTEN is thought to regulate p53 stability, and p53 to enhance PTEN transcription 6-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

119
1,747
10
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,794 publications
(1,891 citation statements)
references
References 30 publications
119
1,747
10
15
Order By: Relevance
“…Previous studies showed that PTEN induces the activation of a p53-dependent cellular senescence response. 13 In the present study, Thomsen et al observed increased cellular proliferation after the loss of both Pten and JunB and decreased expression of the cell cycle inhibitors p16 Ink4a and p21 CIP1 , which are key inducers of cellular senescence (Figure 1). 14 These findings were supported by data from three different gene expression data sets of human PCa samples, were low-grade tumors express JUNB, but high-grade and metastatic tumors are devoid of JUNB and p21 CIP expression.…”
supporting
confidence: 56%
“…Previous studies showed that PTEN induces the activation of a p53-dependent cellular senescence response. 13 In the present study, Thomsen et al observed increased cellular proliferation after the loss of both Pten and JunB and decreased expression of the cell cycle inhibitors p16 Ink4a and p21 CIP1 , which are key inducers of cellular senescence (Figure 1). 14 These findings were supported by data from three different gene expression data sets of human PCa samples, were low-grade tumors express JUNB, but high-grade and metastatic tumors are devoid of JUNB and p21 CIP expression.…”
supporting
confidence: 56%
“…Like apoptosis, senescence has been proposed as a tumor suppressor mechanism (Braig et al, 2005;Chen et al, 2005;Collado et al, 2005;Lazzerini Denchi et al, 2005;Michaloglou et al, 2005). In normal cells, genotoxic and oncogenic stress activate the p53-p21 and p16-pRB pathways, respectively, leading to transient or permanent growth arrest.…”
Section: Clinical Relevance Of Cell Death Pathwaysmentioning
confidence: 99%
“…33 Akt activation is inhibited by the tumor suppressor gene PTEN, suggesting that loss of PTEN, a frequent abnormAndrogen receptor and prostate cancer E Richter et al ality detected in advanced prostate cancer, may lead to progression to androgen independence in CaP. [34][35][36][37] …”
Section: Ar and Signal Transductionmentioning
confidence: 99%